Experimental manipulation of food distribution alters social networks and information transmission across environments in a food-caching bird. (November 2022) - Heinen, Virginia K.; Benedict, Lauren M.; Sonnenberg, Benjamin R.; Bridge, Eli S.; Farine, Damien R.; Pravosudov, Vladimir V.
Abstract : While many animals utilize socially transmitted information, there is still much to understand about how individuals form social networks and how these networks influence social information use. Here, we tested the hypothesis that food distribution and availability can influence social structure and social information transfer when discovering novel food sources. We experimentally manipulated distribution and access to food in wild food-caching mountain chickadees, Poecile gambeli, by randomly dividing existing individuals between two feeding locations, with birds only allowed to obtain food at one of the two locations. We carried out such manipulations at multiple sites associated with two montane elevations of different environmental harshness, where birds show differing use of social information. Following 2 weeks of manipulation, we measured social networks and then introduced novel feeders to test how the manipulation affected social information use. The manipulations effectively split the resident chickadees at both elevations into two distinct communities, and when subsequently discovering novel feeders, information transmission about novel food sources followed the new, rather than the premanipulation, network structure at both elevations, although low-elevation birds used social information more than high-elevation birds. Our data show that chickadees can quickly adjust their social associations in response to short-term changes in the distribution of available resources and that these changes influence who they learn from socially when searching for food. Overall, we observed that chickadees are highly flexible in their use of social information despite their rather stable social group structure and that this information use reflects the most current social environment that individuals experience. Highlights: Mountain chickadee social networks changed during short-term resource manipulation. Social information transmission primarily followed the most recent network edges. Birds at high elevations showed less social information transmission.